Dificuldades encontradas no programa de revacinação dos pacientes submetidos ao transplante de células tronco hematopoiéticas - Silva, Paula Moreira da [UNESP] (2016)
A revaccination program is recommended for all HSCT recipients. Despite the excellence of the Brazilian revaccination program, several pitfalls have been observed over the years. We evaluated such pitfalls and how a prospective and tailored follow-up may help to overcome these obstacles. HSCT recipients (n=122) were followed prospectively and categorized into Group 1 (n=72), recipients who had already started the revaccination program and Group 2 (n=50), recipients who were up to start the vaccines. Whenever a gap on the program was encountered or a difficulty was reported, interventions and subsequent evaluations were performed. Problems related to patient compliance were less frequent than those related to HSCT center modifications of previous recommendations, or to errors made by the vaccination center. Advisory intervention was needed in 64% and 46% of Group 1 and Group 2, respectively (p=0.05), and were partially successful in around 70% of the cases. Total resolution was achieved in more than 35% in both groups. Although the Brazilian revaccination program is excellent, it needs to be improved and all efforts should be made to guarantee a safe and complete revaccination schedule. HSCT centers should appoint nurses and transplant infectious disease physicians to organize and to monitor the progress of the program.